Ground wētā in vines of the Awatere Valley, Marlborough: biology, density and distribution. Issue 4 (1st October 2016) - Nboyine, JA; Boyer, S; Saville, D; Smith, MJ; Wratten, SD
ABSTRACT: The endemic New Zealand ground wētā ( Hemiandrus sp. 'promontorius') has a Naturally Uncommon conservation status. This is because of the paucity of information on its density and distribution. Here, the biology, density and distribution of a population of this wētā found in and around vineyards in the Awatere Valley, Marlborough was studied. Wētā density was assessed in vineyards, paddocks and shrublands in this valley. Soil moisture, penetration resistance, pH and organic matter were recorded at locations with and without wētā. Wētā density in vineyards was significantly higher than in either paddocks or shrub habitats. In vineyards, the density of this insect was significantly higher under-vines than in the inter-rows. Higher numbers of this wētā were found in moist soils that required lower force to burrow. Females laid an average of 55 eggs between March and April, which hatched in September. These findings highlight the intersection between agriculture and conservation.